Downregulation of miR‐1225‐5p is pivotal for proliferation, invasion, and migration of HCC cells through NFκB regulation. Issue 11 (28th July 2020) - Liu, Lin; Zhang, Weiguo; Hu, Yujing; Ma, Liangliang; Xu, Xiangsu
Abstract: Background: As one of the most frequently seen malignancies, hepatocellular carcinoma (HCC) serves as the second largest contributor to malignancy‐specific mortality worldwide. MicroRNA‐1225‐5p (miR‐1225) exerts an essential impact on the growth and metastasis of many malignancies. However, the contribution of miR‐125 to HCC and the molecular mechanism of cancer cell viability and apoptosis are still unclear. We focused our research on exploring the function and molecular mechanism of miR‐1225 in regulating HCC cell growth, migration, and invasion. Material: Quantitative PCR data showed that miR‐1225 expression was repressed in HCC cell lines and in the tissues of HCC patients, compared to that in normal human hepatic cells and tissues. Transfection of a miR‐1225 mimic inhibited cell viability and proliferation as indicated by CCK‐8 staining and MTT assay. Transwell invasion, wound healing assay, and Western blotting were performed to assess whether miR‐1225 repressed the metastasis and invasion of HCC cells, and decreased matrix metalloproteinase 9 (MMP9) expression. Further bioinformatic prediction and dual‐luciferase reporter assay suggested that miR‐1225 targeted the 3′‐UTR of NFκB p65. Results: Overexpression of p65 protein counteracted the repressive impact of miR‐1225 on invasion, migration, and proliferation of HCC cells. Conclusion: This research provided new evidences that miR‐1225 inhibits the viability, migration, and invasion of HCC cells by downregulation of p65. Abstract : NFκB p65 is involved in miR‐1225‐inhibited proliferation, invasion, and migration of HepG2 and Huh‐7 cells. (A, B) HepG2 and Huh‐7 cells underwent co‐transfection with of pCDNA3‐p65/pCDNA3 and the miR‐1225 mimic to upregulate the p65 expression. (A, C) qPCR and (B, D) WB were performed to detect the p65 protein expression in both HCC cell lines. (E, F) Proliferation of Huh‐7 and HepG2 cells was measured at 12, 24, 36, 48, 60, and 72 h after transfection, using the MTT assay. (G, H) Invasion and (I, J) migration of HepG2 and Huh‐7 cells was examined using the Transwell migration test and wound healing assay. Outcome is displayed as mean ± SD. * P  < .05 vs control group.